Stochastic wireless network model - Klavdiiev, Viacheslav; Poliakova, Tetiana (National Technical University "Kharkiv Polytechnic Institute", 2025)
This paper considers an approach to routing optimization based on modeling a sensor network in the form of a Markov decision process (MDP). This model allows formalizing the process of changing node states and making decisions in the form of a mathematical apparatus that can take into account the probabilities of transitions between states, rewards for certain actions, and also provide a search for the optimal information transmission strategy taking into account QoS and energy conservation.
Keywords: telecommunication networks; sensor network; stochastic process; quality of service; Markov processes